Ut musica poesis : une formule impertinente et féconde pour penser l’opéra français des 17e et 18e siècles - Sarah Nancy (Etudes Epistémè)
The concept of Ut musica poesis, which has so often been used in studies of literature and music in the last thirty years, does not really account for the French opera of the 17th and 18th centuries. Far from positing the existence of a musical order as a model for language, the genre highlights intelligibility as a principle. This can be explained by the predominance of the dramatic model of representation, which is consistently formulated in visual terms, but also by the perception of music as the « dark song » of language, capable of making speech dynamic but also of introducing an uncanny disorder into it. Against the formula of Ut musica poesis, the French opera of the period known as « Classical » shows how poetics and rhetoric meet through a non-aesthetic conception of music seen as inseparable from language, which means its effects must be received with the utmost seriousness. The seemingly irrelevant formulation Ut musica poesis thus proves nevertheless fruitful. It invites the critic to reconsider the oppositions between interest and pleasure, efficiency and abandon, disinterestedness and involvement, and eventually to consider art’s ability to produce political effects.